Benchmark your department, team for professional development success. Issue 7 (18th October 2022) - Skipworth, Stan
Abstract : As another year steadily comes to its end and makes room for another, we all seemingly begin to allow ourselves time to consider new goals we wish to achieve. These may be personal — perhaps to accomplish a new level of health or fitness, completing an academic endeavor, or tackling a home improvement project. These goals could also be professional: seeking to gain a key assignment or promotion, or completing a training course that expands and enhances our skill sets.